Characteristics of Poor Recordability of Intraoperative Neurophysiological Monitoring during Metastatic Spinal Tumor Surgery: A Multicenter Study - Naoki Segi; Hiroaki Nakashima; Masahiro Funaba; Jun Hashimoto; Shigenori Kawabata; Masahito Takahashi; Go Yoshida; Hiroki Ushirozako; Kenta Kurosu; Hideki Shigematsu; Tsunenori Takatani; Shinji Morito; et al. (Spine Surgery and Related Research)
Introduction: The objective of this study is to investigate the poor recordability characteristics of intraoperative neurophysiological monitoring (IONM) for metastatic spinal tumors, focusing on tumor status or preoperative muscle weakness. Methods: A total of 132 patients (age 65.3±11.8 years; 82 men) with or without preoperative lower extremity muscle weakness were included in this study. The patients' background characteristics, the presence and degree of pre- and postoperative muscle weakness, and the IONM outcome, including the availability of transcranial motor evoked potential (Tc-MEP) recording and the occurrence of Tc-MEP alarms, were investigated. The data between the groups with and without preoperative muscle weakness were compared. Logistic regression analysis was performed to identify the risk factors for unrecordable Tc-MEP. Results: Sixty-seven patients with muscle weakness had significantly more unrecordable Tc-MEP (19% vs. 5%, p=0.009) than the 65 patients without muscle weakness. The highest percentage of recordable Tc-MEP in the group with muscle weakness was noted in the plantar muscle (72%). Multivariate analysis identified manual muscle test (MMT) score of 3 (odds ratio [OR] 4.529) and ventral spinal cord compression by metastatic tumor (OR 3.924) as independent significant factors for unrecordable Tc-MEP. Conclusions: IONM for metastatic spinal cord tumors with muscle weakness had a high rate of unrecordable Tc-MEP. Additionally, Tc-MEP may not be detectable in cases of ventral spinal cord compression by a tumor; therefore, preoperative imaging should be thoroughly evaluated.